Modal Analysis of the Cycloid Gear Pump based on Pro/E and ANSYS - Zhao Han; Tang Kaicong; Huang Kang; Sun Yingbo; Sha Faming (Jixie chuandong)
By using the three-dimensional CAD software Pro/E,the three-dimensional geometric model of a certain type of cycloidal gear pumps is established,then the mesh generation of them is carried out by using Hypermesh,and it is simplified and imported into ANSYS software,the finite element model is built.Using the ANSYS software,the modal analysis of cycloidal gear pump is carried out,the modes,natural frequency and mode shapes participation factor of cycloid gear pump are acquired to ensure in the design of cycloid gear pump can avoid resonance model.The results show that the cycloid gear pump design is reasonable,and the results of modal analysis can be provide an important frame of reference for the optimum structural design and the development of new products.